Oral mucosa immunity: ultimate strategy to stop spreading of pandemic viruses - Jang, Hyesun; Matsuoka, Michele; Freire, Marcelo (Frontiers in Immunology, 2023)
Global pandemics are most likely initiated via zoonotic transmission to humans in which respiratory viruses infect airways with relevance to mucosal systems. Out of the known pandemics, five were initiated by respiratory viruses including current ongoing coronavirus disease 2019 (COVID-19). While striking progress in vaccine development and therapeutics have helped ameliorate the mortality of infectious agents, viral replication and virus spread through mucosal tissues cannot be directly controlled by parenteral vaccines. A novel mitigation strategy is needed to elicit robust mucosal protection and broadly neutralizing activities to hamper virus entry mechanisms and inhibit transmission. This review focuses on the oral mucosa, which is a critical source of viral transmission and promising target to elicit sterile immunity. In addition to reviewing historic pandemics initiated by the zoonotic respiratory RNA viruses and the oral mucosal tissues, we discussed unique features of the oral immune responses. We address barriers and new prospects related to developing novel therapeutics to elicit protective immunity at the mucosal level to ultimately control transmission.